INTEGRATION AS A TREND IN THE DEVELOPMENT OF PEDAGOGY - Tairov Sherzod Mirzadjanivich (Zeta Repository, 2023)
This article outlines the essence of the concept of integration and the importance of integration in the development of pedagogy.